Organizational responsiveness: The case of unfolding crises and problem detection within HELCOM. (August 2016) - Valman, Matilda; Duit, Andreas; Blenckner, Thorsten
Abstract: How and to what extent do international organizations detect, process and react to different types of change within their policy domains? This study addresses this question by combining a unique data set consisting of policy documents from the Helsinki Commission (HELCOM) with data measuring ecosystem change in the Baltic Sea during the period 1980–2013. Here HELCOM's responses to two types of ecosystem changes are investigated: fast and visible (summer algae blooms) and slow and opaque (anoxic areas). Finally, this study assesses if the organizational reform of 2007, which introduced the ecosystem approach, has had any effects on HELCOM responsiveness. It is found that HELCOM, contrary to expectations, is only responding systematically to slow-moving and opaque processes but that this response confirms the anticipated organizational bottom-up pattern. The ecosystem approach reform seems to have had a negative effect on the responsiveness of HELCOM; however, a general trend is that HELCOM over time has become more responsive in the lower levels of the organization. The lack of an immediate effect regarding the ecosystem approach reform can serve as a reminder of the absence of panaceas in policy making in general, and in environmental governance in particular. Highlights: HELCOM is only responding systematically to slow-moving and opaque processes. The BSAP reform have had no direct effect on the organizational responsiveness. HELCOM have over time have become more responsive in lower organizational levels. Lower levels of HELCOM are fairly good at detecting and reacting to changes.